Influence of genotype, nodule position, and edaphic factors on microbial diversity and assembly of pigeonpea (Cajanus cajan) root nodules in Indian soils - Anirban Basu; Danteswari Chalasani; P.V.S.R.N. Sarma; Sheetal Uikey; Vijaya Ranganatha Chenna; Pushpajeet Lokpal Choudhari; Appa Rao Podile (Environmental Microbiome)
Abstract Background Pigeonpea (Cajanus cajan) is an important legume crop in semi-arid regions with multiple uses. The microbial diversity within its root nodules in Indian soils remains poorly explored. We investigated the bacterial diversity of pigeonpea root nodules across different genotypes and soil types to identify the factors driving their assembly. Using a metagenomic approach and high-throughput sequencing of the 16S rRNA gene, we analyzed the nodule microbiomes of three pigeonpea genotypes (Asha, Durga, and Mannem Konda Kandi) grown in three different soil types (Alfisol, Vertisol, and Inceptisol) and wild pigeonpea (C. scarabaeoides) in its native soil. Results Our results indicated that pigeonpea nodules harbor diverse rhizobial and non-rhizobial endophytes and that host genotype, nodule position, soil type, and other edaphic factors influence significant variation in the microbial community structure. The core nodule microbiome was dominated by Proteobacteria and Bacteroidetes. Bradyrhizobium and Ensifer were predominant among the rhizobial taxa, and non-rhizobial genera such as Pseudomonas, Chitinophaga, and Limnobacter were also abundant. Edaphic factors, particularly soil type, pH, and nutrient availability, had a stronger influence on the nodule bacterial community composition than the host genotype. Although bulk soil exhibited higher bacterial diversity, nodule microbiomes were less diverse but more specialized, indicating host-mediated selection. A comparison of the nodule microbiomes of wild and cultivated pigeonpea revealed distinct differences, with the core nodule microbiome of wild pigeonpea dominated by Bradyrhizobium, while that of cultivated pigeonpea exhibited a diverse bacterial community. Conclusions These findings demonstrate that soil properties play a more critical role than host genetics in shaping the pigeonpea nodule microbiome, emphasizing the importance of environmental conditions in symbiotic interactions. The differences between wild and cultivated genotypes suggest that domestication has altered microbial recruitment strategies. This study provides foundational insights into the factors driving microbial assembly in pigeonpea nodules, with implications for improving crop productivity through targeted microbial management. Future research should explore the functional roles of these microbial communities to optimize their use in sustainable agriculture.